The Best Anticoagulation Strategy for Cirrhotic Patients who Underwent Splenectomy: A Network Meta-Analysis - Cheng Gong; Xian Qin; Jian Yang; Tao Guo (Gastroenterology Research and Practice)
Objective. To determine the best anticoagulation strategy for the patients who underwent splenectomy with cirrhosis through network meta-analysis. Methods. We conducted a systematic review of the literature in PubMed, Embase, and the Cochrane Library database. We extracted data on incidence of Portal vein system thrombosis (PVST) from studies that compared various anticoagulation strategies for use with patients who underwent splenectomy with cirrhosis. Network meta-analysis was conducted in ADDIS by evaluating the different incidence of PVST. Consistency and inconsistency models were developed to identify differences among the therapeutic strategies. Cumulative probability was utilized to rank the strategies under examination. Results. A total of 11 studies containing 1153 patients were included in the network meta-analysis. The results revealed that the application of Antithrombin III was the best anticoagulation option for patients who underwent splenectomy with cirrhosis (P=0.59). The data of consistency and inconsistency models exhibited basically consistent and showed good convergence. Conclusions. Application of Antithrombin III seemed to be the best anticoagulation strategy for cirrhotic patients who underwent splenectomy and should be considered a first-choice clinical reference.